Edgar Sydenstricker, a pioneer of health economics - Clarke, P; Erreygers, G (Taylor and Francis, 2022)
The economist Edgar Sydenstricker, who spent most of his working life at the United States Public Health Service and at the Milbank Memorial Fund, examined a wide range of health economics issues. He contributed to the debate around the cause of the disease pellagra. This research was followed by many studies quantifying income-related health inequalities. Sydenstricker was heavily involved in the use of surveys to collect information and he was instrumental in the development of the first US National Health Survey. Other contributions include extending health insurance in the United States and methods of evaluating public health programs.